Reduced plasma oxytocin levels in female patients with borderline personality disorder - Bertsch, Katja; Schmidinger, Ilinca; Herpertz, Sabine (Hormones and behavior, 2013)
The neuropeptide oxytocin is involved in social cognition and interaction across species and plays a crucial role in the regulation of affiliative behaviors. Oxytocin levels in cerebrospinal fluid (CSF), but also in plasma or urine, have been shown to be negatively associated with childhood traumata, aggressive behavior, and suicide attempts. Recently, an altered activity of the oxytocin system has been discussed to play a prominent role in borderline personality disorder (BPD), which is thought to be closely related to traumatic experiences in childhood and is characterized by (para)suicidal behaviors as well as aggressive outbursts. In the present study, we compared plasma oxytocin levels of women with and without BPD in the follicular phase and assessed the relationship between oxytocin concentrations and childhood traumata. Women diagnosed with BPD had significantly reduced oxytocin concentrations, even after controlling for estrogen, progesterone, and contraceptive intake. In addition, plasma oxytocin correlated negatively with experiences of childhood traumata, in particular with emotional neglect and abuse. The results of mediation analyses do not support a model of oxytocin being a prominent mediator in the link between childhood trauma and BPD. Thus, the findings indicate dysregulations in the oxytocin system of patients diagnosed with BPD with more longitudinal research being necessary to disentangle the relationship between childhood adversities, oxytocin system, and psychopathology.